Earnings Less Risk-Free Interest Charge (ERIC) and stock returns - a value-based management perspective on ERIC's relative and incremental information content - Rainer Lueg; Jon Svennesen Toft (Journal of Risk and Financial Management, 2022)
This paper investigates the relative and incremental information content of KPMG's recently developed metric for shareholder value creation: earnings less risk-free interest charge (ERIC). We assess if ERIC has a better ability to predict stock returns than earnings, cash flow from operations (CFO), earnings before extraordinary items (EBEI), residual income (RI), or economic value added (EVA). We evaluate data from 214 companies listed on the U.S. Standard & Poor's 500 Index from 2003 to 2012 (2354 firm-year observations). Similar to previous studies, we confirm that CFO and EBEI have the strongest association with stock returns in the short term, while EVA trails behind all other metrics. In terms of new findings, ERIC is the best predictor of stock returns over a 5-year period, as well as during times of crises (from 2009 to 2010). In this period, ERIC also adds incremental information content beyond that of EBEI. However, the low-short-/mid-term predictive ability of shareholder value metrics (EVA, ERIC) raises concerns regarding their reliable use in future research on shareholder value creation. We consequently propose a research agenda that focuses less on the measurement and more on the management of shareholder value.
Keywords: 650; earnings less risk-free interest charge; economic value added; incremental information content; relative information content; shareholder value; value-based management